INOVASI TRANSPORTASI UMUM WIRA-WIRI SEBAGAI STRATEGI DINAS PERHUBUNGAN KOTA SURABAYA UNTUK MENINGKATKAN AKSESIBILITAS DAN MOBILITAS PUBLIK - zaky, zaky; Taufiq, Amal (Universitas Islam Negeri Sunan Ampel, 2025)
In a metropolis like Surabaya, public transportation is a vital component of promoting mobility. The objective of this study is to evaluate the Surabaya City Transportation Agency's initiatives in offering Wira-Wiri public transportation services as a form of public mobility. A qualitative approach is used, with data collected through observation, interviews with Transportation Agency staff and Wira-Wiri passengers, and documentation from numerous sources. According to the study, the Transportation Agency has enhanced its services by adding more fleets, creating and integrating routes between transportation methods, and implementing an integrated ticketing system that is simpler for consumers to use. The primary goal of other policies, such as fair fares and service quality monitoring, is to guarantee passenger comfort and safety. Despite the challenges in tracking implementation, this initiative has greatly improved access to public transportation. This research highlights the need for collaboration between the community, operators, and the government in order to create public transit that is productive, environmentally friendly, and improves the quality of life for Surabaya citizens.